Corporate governance, competition, and political parties : explaining corporate governance change in Europe - Barker, Roger M. (Oxford : Oxford University Press, 2010)
Significant changes in corporate governance in continental Europe have been increasingly evident in the last decade. This book argues that firms in some of these countries have eschewed the traditional stakeholder-orientation for a strategy based on the maximization of shareholder value, despite a period of social democratic politics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Corporate governance -- Europe; Stockholders -- Europe; Competition -- Europe; Organizational change -- Europe; Corporations -- Investor relations -- Political aspects -- Europe